Synergistic effect of Pd+Rh on the microstructure and oxidation resistance of aluminide coatings - Zagula-Yavorska, Maryana (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The Pd+Rh modified aluminide coatings were deposited on nickel and CMSX-4 nickel superalloy. The Pd layer (2.5 µm thick) and the subsequent Rh layer (0.5 µm thick) were electroplated on both nickel and CMSX-4. The aluminization of the substrates with Pd+Rh layers was carried out using the CVD method.  Two zones (outer and interdiffusing) were observed on both coatings. The β-NiAl phase doped in palladium was formed in the outer zones and β-NiAl phase doped with palladium and rhodium was formed at the boundary between the outer and interdiffusion zones of both coatings. The γ’-Ni3Al phase and μ-Co7Mo6 precipitates in the β-NiAl matrix were found in the interdiffusion zone on nickel and CMSX-4 superalloy respectively.  The simultaneous use of Pd and Rh in the aluminide coating slowed down their oxidation rate. Moreover, Pd+Rh co-doping is more efficient than Pd+Hf in reducing the oxidation rate of aluminide coating on CMSX-4 superalloy.
Keywords: Pd Rh, aluminide coating, oxidation, kp value